Ancient Sites, History and Local Wisdom: Tourism Boosting Reforms to Improve the Economy and Living Standard in the Province of Bengkulu, Indonesia. (23rd September 2021) - Ardilafiza,; Warman, Kurnia; Illahi, Beni Kurnia; Tegnan, Hilaire
Law No. 6/2014 on Villages provides for sustainable community empowerment at the village level through the development of ancient sites, and local wisdoms through the tourism village concept in Indonesia. Because a vast majority of its population depends on agriculture and tourism for sustenance, the regional government of the Bengkulu Province is making reforms to improve its large tourism sector consisting of numerous pristine ancient sites, culture and local wisdom. However, this sector, so vital to the region and beyond, has not been very productive for both the local government and more importantly the population of Bengkulu. Attempting the address the question as to how to design an ideal tourism boosting policy and regulations to improve the economy of Bengkulu Province, this research aims to identify and analyze the dynamics of village-related regulations dealing with the management of tourist attractions, including tourism village concept in Bengkulu Province. In so doing the study also seeks to analyze the arrangement and management of village wealth so that it can be developed into a tourist attraction based on local wisdom in the context of economic development that favors both the community and the local government in Bengkulu Province. This study reveals that the shortcoming in the management of touristic resources in the Bengkulu Province lies in several issues including the lack of regional policies and regulations that prioritize community participation, poor organization and management of the program, bad governance and the control of the program by thugs, hence eroding the possibility for accountability.